Предмет: Алгебра,
автор: mitkin01
(x-1)+(12-7,5x)=
(2p+1,9)-(7-p)=
(3-0,4a)-(10-0,8a)=
Ответы
Автор ответа:
0
1)(x-1)+(12-7,5x)=x-1+12-7,5x=11-6,5x
2) (2p+1,9)-(7-p) = 2p+1,9 -7 + p = 3p - 5,1
3) (3-0,4a)-(10-0,8a) = 3 - 0,4 a - 10 +0,8a = -7 +0,4a
2) (2p+1,9)-(7-p) = 2p+1,9 -7 + p = 3p - 5,1
3) (3-0,4a)-(10-0,8a) = 3 - 0,4 a - 10 +0,8a = -7 +0,4a
Похожие вопросы
Предмет: Литература,
автор: Аноним
Предмет: Геометрия,
автор: fotioneone
Предмет: Музыка,
автор: mosinakv
Предмет: Химия,
автор: mikisheva98
Предмет: Алгебра,
автор: Perst04